2011
DOI: 10.3892/ol.2011.500
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of P-glycoprotein expression by triptolide in adriamycin-resistant K562/A02 cells

Abstract: Abstract. Multidrug resistance is a serious obstacle encountered in leukemia treatment. Previous studies have found drug resistance in human leukemia is mainly associated with overexpression of the multidrug resistance gene 1 (MDR1). The aim of the present study was to investigate the modulation of P-glycoprotein expression by triptolide in adriamycin-resistant K562/A02 cells. The reverse effects of triptolide on drug resistance in K562/A02 cells were assessed by 3-[4,5-dimethylthiazol-2-yl]-2, 5-diphenyl-tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Quercetin decreased cell number through the induction of apoptotic cell death in AGS cells that were measured by Annexin V/PI double staining and then were analyzed by flow cytometric assay. It is well documented that Annexin V/PI staining is a protocol for measuring and quantitating the percentage of apoptotic cell death . We also found that quercetin induces apoptotic cell death through ER stress in AGS cells based on ROS production and ATF‐6α, ATF‐6β, and GRP‐78 that were the hall markers of ER stress .…”
Section: Discussionsupporting
confidence: 51%
“…Quercetin decreased cell number through the induction of apoptotic cell death in AGS cells that were measured by Annexin V/PI double staining and then were analyzed by flow cytometric assay. It is well documented that Annexin V/PI staining is a protocol for measuring and quantitating the percentage of apoptotic cell death . We also found that quercetin induces apoptotic cell death through ER stress in AGS cells based on ROS production and ATF‐6α, ATF‐6β, and GRP‐78 that were the hall markers of ER stress .…”
Section: Discussionsupporting
confidence: 51%
“…f. It possesses efficient antitumor activity against a range of cancer cells. TPL has been demonstrated to exert its reversal activity on various MDR cancer cells, mainly through the downregulation of MDR proteins, including P-glycoprotein (17)(18)(19). Our primary study revealed that TPL could notably inhibit the proliferation of a panel of MDR cancer cell lines, including A549/Taxol, MCF-7/ADR and Bel7402/5-Fu (20).…”
Section: Discussionmentioning
confidence: 99%
“…The efflux of anticancer drugs from tumor cells depends on P‐gp (Oga et al, 2012). Rhodamine‐123 is a well‐established P‐gp substrate to investigate the activity of the P‐gp by the detection of intracellular fluorescence by flow cytometry (Clark et al, 1996; Li et al, 2012). The results indicated that TFPI‐2 overexpression BEL‐7402/5‐FU cells enhanced the accumulation of rhodamine‐123 to 2.50‐fold and 2.85‐fold levels when compared with parent and negative control cells (Fig.…”
Section: Resultsmentioning
confidence: 99%